A Low-Noise Micromachined Accelerometer with Reconfigurable Electrodes for Resonance Suppression - Zayed Ahmed; Charles Duruaku; Fatemeh Edalatfar; Mehrdad Moallem; Behraad Bahreyni (Micromachines, 2023)
We present a high-performance capacitive accelerometer with a sub-µg noise limit and 1.2 kHz bandwidth for particle acceleration detection applications. The low noise of the accelerometer is achieved through a combination of device design optimization and operation under vacuum to reduce the effects of air damping. Operation under vacuum, however, causes amplification of signals around the resonance region, potentially resulting in incapacitating it through saturation of interface electronics or nonlinearities and even damage. The device has thus been designed with two sets of electrodes for high and low electrostatic coupling efficiency. During normal operation, the open-loop device utilizes its high-sensitivity electrodes to provide the best resolution. When a strong signal near resonance is detected, the electrodes with low sensitivity are used for signal monitoring, while the high-sensitivity electrodes are used to apply feedback signals efficiently. A closed-loop electrostatic feedback control architecture is designed to counteract the large displacements of the proof mass near resonance frequency. Therefore, the ability to reconfigure electrodes lets the device be used in high-sensitivity or high-resiliency modes. Several experiments were conducted with DC and AC excitation at different frequencies to verify the effectiveness of the control strategy. The results showed a ten-fold reduction of displacement at resonance in the closed-loop arrangement compared to the open-loop system with a quality factor of 120.